The happiness of small-scale dairy farmers: A case at Malang Regency of East Java, Indonesia - Sutawi, S.; Prihartini, I.; Khotimah, K.; Iswatiningsih, D.; Kusumastuti, F. (Diponegoro University, 2022)
This study was conducted to assess the happiness of small-scale dairy cattle farmers based on subjective well-being conditions. The research was conducted in July-October 2020 using a survey method in the Malang Regency of East Java Province. Analysis units were 145 small-scale dairy cattle farmer households purposively selected with less than 30 heads of dairy cattle ownership and have managed their livestock farming for more than five years. Data collection was conducted through interviews about three dimensions of happiness including life satisfaction, affection, and the meaning of life. The three dimensions were divided into 19 indicators to calculate the Happiness Index. The ten Life Satisfaction indicators produced a Life Satisfaction Index of 7.43 (Happy), consisting of a Personal Life Satisfaction Index of 7.26 (Happy) and a Social Life Satisfaction Index of 7.85 (Happy). The three Affection indicators produced the Affection Index of 7.29 (Happy). The six Meaning of Life indicators produced the Meaning of Life Index of 7.44 (Happy). The Happiness Index of small-scale dairy cattle farmers in East Java was 7.43 and classified as